2011
DOI: 10.1097/mnh.0b013e328341164a
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 is a key modulator of the renin–angiotensin system in cardiovascular and renal disease

Abstract: Repletion of ACE2's activities offers a new strategy to complement current clinical interventions in treating hypertension, renal and cardiovascular disease. In particular conditions where ACE inhibition and angiotensin receptor blockade are partially effective, the adjunctive actions of ACE2 may not only reduce clinical escape but also augment the efficacy of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
144
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 72 publications
6
144
0
3
Order By: Relevance
“…2 Increasing evidence shows that Ace2 has an essential role in the cardiovascular and kidney diseases. 1,3,4 Ace2 inhibition also leads to the development of albuminuria in a mouse model of diabetes. 5,6 Direct evidence for ACE2 in the development of hypertensive kidney disease comes from the Ace2 gene knockout mice.…”
mentioning
confidence: 99%
“…2 Increasing evidence shows that Ace2 has an essential role in the cardiovascular and kidney diseases. 1,3,4 Ace2 inhibition also leads to the development of albuminuria in a mouse model of diabetes. 5,6 Direct evidence for ACE2 in the development of hypertensive kidney disease comes from the Ace2 gene knockout mice.…”
mentioning
confidence: 99%
“…The ACE2 gene has been implicated in kidney disease, hypertension and cardiac function. 32 Previous studies have also shown that expression of the ACE2 gene is altered in the diabetic rat kidney 33 and in humans with renal diseases. 34 This suggests that an association exists between ACE2 gene variants and ESRD.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the degradation of Ang II is also important, 34 and the major enzyme that converts Ang II to Ang 1-7 is ACE2. 35 So, it is the balance between ACE and ACE2 that is currently considered critical for the activation of renal RAS. 36,37 Having said that, the second novel aspect of this work is that we show the effect that aldosterone, alone and in combination with salt, has on ACE2 glomerular expression in vivo.…”
Section: Discussionmentioning
confidence: 99%